Implementation of the Policy on the Construction of Cheap Houses for Low-Income Communities in Palembang City, South Sumatera Province - Hamdi Darmawan; Ermaya Suradinata; Rossy Lambelanova; Sampara Lukman (International Journal of Science and Society, 2021)
As one of the oldest cities in Indonesia, Palembang City is included in the ranks of the most populated cities in Indonesia. It should pay attention to the social life of its people, especially in terms of place of residence and residence. Since the issuance of Law Number 1 of 2011 and Government Regulation Number 64 of 2016 concerning low-cost housing, it has not been running optimally. Therefore, researchers are interested in researching implementing low-cost housing policies in the city of Palembang. This research uses qualitative methods with observation techniques, in-depth interviews with informants supported by various related documents. This study uses the concept of wisdom, the process of implementing wisdom, the factors that influence the implementation of wisdom. The results of this study indicate that the performance of low-cost housing for the people in Palembang City has not been optimal due to various dominant factors, namely communication and conflicts of interest between agencies so that it requires a strategy by carrying out different incremental policies such as regulatory reform, increasing resources, forming public opinion, and cooperation. With private parties.